Mouse Model of Congenital Heart Defects, Dysmorphic Facial Features and Intellectual Developmental Disorders as a Result of Non-functional CDK13 - Nováková, Monika; Hampl, Marek; Vrábel, Dávid; Procházka, Jan; Petrezselyová, Silvia; Procházková, Michaela; Sedláček, Radislav; Kavková, Michaela; Zikmund, Tomáš; Kaiser, Jozef; Juan, Hsien-Chia; Fann, Ming-Ji; et al. (Frontiers in Cell and Developmental Biology, 2019)
Congenital heart defects, dysmorphic facial features and intellectual developmental disorders (CHDFIDD) syndrome in humans was recently associated with mutation in CDK13 gene. In order to assess the loss of function of Cdk13 during mouse development, we employed gene trap knock-out (KO) allele in Cdk13 gene. Embryonic lethality of Cdk13-deficient animals was observed by the embryonic day (E) 16.5, while live embryos were observed on E15.5. At this stage, improper development of multiple organs has been documented, partly resembling defects observed in patients with mutated CDK13. In particular, overall developmental delay, incomplete secondary palate formation with variability in severity among Cdk13-deficient animals or complete midline deficiency, kidney failure accompanied by congenital heart defects were detected. Based on further analyses, the lethality at this stage is a result of heart failure most likely due to multiple heart defects followed by insufficient blood circulation resulting in multiple organs dysfunctions. Thus, Cdk13 KO mice might be a very useful model for further studies focused on delineating signaling circuits and molecular mechanisms underlying CHDFIDD caused by mutation in CDK13 gene.